2014
DOI: 10.1002/cphc.201301204
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Interactions of Trityl Groups

Abstract: Trityl group, Tr, is a molecular dynamic rotor of which the conformation and helicity depend on other groups in the close vicinity. Interactions with another covalently linked Tr group and with other substituents are analyzed in terms of transfer of chirality to the trityl group. Two trityl groups in a molecule can mutually interact at a distance of two, three, or five bonds. Despite its size, a Tr group attached to a cyclohexane or cyclopentane ring through an oxygen or nitrogen atom adopts either an axial or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…6 Meanwhile, introduction of an amide linker between the inductor and the receptor caused a signicant increase of this distance, which resulted in consequent lack of involvement of the two reporter units in mutual steric interactions. For ditrityl ethers and amines the structural feature that served to identify mutual interactions of the trityl groups was their conformationthe trityls that were not involved in steric interactions had an approximate C 3 -symmety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Meanwhile, introduction of an amide linker between the inductor and the receptor caused a signicant increase of this distance, which resulted in consequent lack of involvement of the two reporter units in mutual steric interactions. For ditrityl ethers and amines the structural feature that served to identify mutual interactions of the trityl groups was their conformationthe trityls that were not involved in steric interactions had an approximate C 3 -symmety.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 6 Only in the case of amide 6 the number of the individual low-energy structures exceeded seven. Computationally found number of thermally accessible conformers was lower than reported previously for N,N 0 -ditrityldiamines or O,O 0 -ditrityldiols.…”
Section: Molecular Structure In Silico and In Crystalmentioning
confidence: 91%
“…Thus, the conformation of the chromophore reflects not only the chiral neighborhood created by stereogenic centers, buta lso the chromophores mustm atch each other.T his situation is characteristicf or molecular propellers such as 1,2-ditrityl derivatives of chiral, nonracemic vicinal diols and diamines. [36] From those findings, the following questions emerged.F irst, what is the origin of the opticala ctivity of the benzhydryl ethers in this study?S econd, are the observed Cotton effects the results of interactions within the isolated chromophore or interactions between chromophores?I no ther words, can we expect exciton coupling between the neighboring benzhydryl groups?T hird, is there any regularity that associates the structure of the chromophorew ith the generated rotatory strengthsresponsible for the observed Cotton effect?…”
Section: Electroniccircular Dichroism Studymentioning
confidence: 99%
“…Of particulari nterest are the chiropticalp roperties of derived benzhydryl ethers attached to achiral molecule. [18] Trityl derivatives of chiral alcohols [19] or chiral amines [20] are alternatives for chromophoric derivatization but they are more difficult to prepare and are less stable. An assembly of ap olar substrate and an onpolar reporting chromophorecan be as ource of valuable The benzhydryl (diphenylmethyl) group is am olecular propeller that can act as ac hirality reporteri fi ti si ntroduced nearby as tereogenic center by making an ether bond.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the usability of the trityl group has been expanded on catalysis and medicinal chemistry [45,46,47]. We and others have shown that the stereodynamic propeller-like trityl group, characterized by P - or M -helicity (i.e., has the sense of a twist of the phenyl groups) [48,49,50,51,52,53,54], when attached to the permanently chiral inducer can act as a chirality reporter adapting its structure to the chiral environment [46].…”
Section: Introductionmentioning
confidence: 99%